2015
DOI: 10.1186/s12885-015-1727-6
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative neutrophil-to-lymphocyte ratio is an independent prognostic marker in patients with laryngeal squamous cell carcinoma

Abstract: BackgroundNeutrophil-lymphocyte ratio (NLR) has been shown to be associated with prognosis in various solid tumors. This study aimed to evaluate the prognostic role of NLR in patients with laryngeal squamous cell carcinoma (LSCC).MethodsA total of 141 LSCC patients were retrospectively reviewed. Patients’ demographics were analyzed along with clinical and pathologic data. The optimal cutoff value of NLR was determined using receiver operating characteristic (ROC) curve analysis. The impact of the NLR and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 31 publications
2
64
0
Order By: Relevance
“…Kum et al [13] found statistical significance between the NLR values and the groups in the study conducted with 209 patients by studying three groups of benign, premalignant, and malignant lesions. In their study of 141 patients, Tu et al [14] found that elevated preoperative NLR was an independent predictor for poor prognosis after surgical resection in patients with LSCC. Gong et al [15] studied 161 patients and found that increased preoperative NLR could contribute to the advanced tumor node metastasis stage of papillary thyroid carcinoma in patients who were older than 45 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kum et al [13] found statistical significance between the NLR values and the groups in the study conducted with 209 patients by studying three groups of benign, premalignant, and malignant lesions. In their study of 141 patients, Tu et al [14] found that elevated preoperative NLR was an independent predictor for poor prognosis after surgical resection in patients with LSCC. Gong et al [15] studied 161 patients and found that increased preoperative NLR could contribute to the advanced tumor node metastasis stage of papillary thyroid carcinoma in patients who were older than 45 years.…”
Section: Discussionmentioning
confidence: 99%
“…[13,14] To the best of our knowledge, this is the first study to suggest that PLR maybe used for PLL and LSCC discrimination. According to the current results PLR may be used for PLL and LSCC discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…Laryngeal squamous cell carcinoma (LSCC) is one of the most common malignancies that remains as a significant cause of morbidity and mortality in head and neck 1. It is estimated that the new cases of laryngeal cancer expected among men and women in China in 2015 are 23,700 and 2,600, respectively; and the estimated number of deaths from laryngeal cancer is about 14,500 2.…”
Section: Introductionmentioning
confidence: 99%
“…Cumulating evidence suggests that increased systemic inflammation might represent a stage-independent unfavorable prognostic factor in different types of cancer 1,1215. Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR), which reflect the systemic inflammation, are readily available and effective predictors of poor survival outcome across various cancers, including intrahepatic cholangiocarcinoma,12 breast cancer,13 colorectal cancer,14 LSCC,1,15 and so on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation